Evidence-based validation of herbal medicine translational research on botanicals - Mukherjee, Pulok K. (Amsterdam, Netherlands Elsevier, 2022)
"Evidence-Based Validation of Herbal Medicines: Translational Research on Botanicals brings together current thinking and practice in the characterization and validation of natural products. The book describes different approaches and techniques for evaluating the quality, safety and efficacy of herbal medicine, particularly methods to assess their activity and understand compounds responsible and their probable underlying mechanisms of action. This book brings together the views, expertise and experiences of scientific experts in the field of medicinal plant research, hence it will be useful for researcher who want to know more about the natural lead with their validation and also useful to exploit traditional medicines."
Includes bibliographical references and index.
Keywords: Herbs -- Therapeutic use; Medicinal plants -- Research; Phytotherapy -- Evaluation